The effects of cognition and visual perception on activities daily living in the elderly - Bae, WonJin; Jung, NamHae (Edelweiss Applied Science and Technology, 2024)
This study aimed to investigate the influence of cognition and visual perception on activities of daily living (ADL) among community-dwelling elderly individuals. Cognition was assessed using the Korean version of Montreal Cognitive Assessment, visual perception was assessed using the Motor Free Visual Perception Test -3, and ADL were assessed using the Modified Barthel Index. The results indicated that cognition, visual perception, and ADL were all positively correlated. Additionally, both cognition and visual perception were found to impact the ADL in the elderly. This study provides evidence that can be used to develop welfare and rehabilitation programs for the elderly, focusing on managing cognitive and visual perception abilities to support independent ADL and enhance quality of life.